Management of collar rot of tomato caused by Sclerotium rolfsii - Indramani Bhagat (Bibechana, 2014)
Collar rot of tomato (Lycopersicum esculentum Miller) caused by Sclerotium rolfsii Sacc. is one of the most destructive diseases in tomato throughout the world. Effective and efficient management of the crop disease is generally achieved by the use of synthetic pesticides. These pesticides are known to pollute the environment, soil and water besides causing deleterious effects on human health and biosphere.